The Role of MicroRNAs in Breast Cancer Migration, Invasion and Metastasis - Joy Tang (International Journal of Molecular Sciences, 2012)
MicroRNAs (miRNAs) are a major class of small, noncoding RNA molecules that regulate gene expression by targeting mRNAs to trigger either translational repression or mRNA degradation. They have recently been more widely investigated due to their potential role as targets for cancer therapy. Many miRNAs have been implicated in several human cancers, including breast cancer. miRNAs are known to regulate cell cycle and development, and thus may serve as useful targets for exploration in anticancer therapeutics. The link between altered miRNA signatures and breast cancer development and metastasis can be observed either through the loss of tumor suppressor miRNAs, such as let-7s, miR-30a/31/34a/125s/200s/203/205/206/342 or the overexpression of oncogenic miRNAs, such as miR-10b/21/135a/155/221/222/224/373/520c in breast cancer cells. Some of these miRNAs have also been validated in tumor specimens of breast cancer patients, underscoring their potential roles in diagnostics, as well as targets for novel therapeutics for breast cancer. In this review article, we will provide an overview and update of our current understanding of the mode of action of several of these well characterized miRNAs in breast cancer models. Therefore, better understanding of the gene networks orchestrated by these miRNAs may help exploit the full potential of miRNAs in regards to cancer diagnosis, treatment, and therapeutics.